Biostratigraphy versus isotope geochronology: Testing the Urals island arc model - Tessalina, Svetlana; Talavera, Cristina; Pritchin, M.; Puchkov, V. (Elsevier, 2018)
Formation of the Urals volcanic-hosted massive sulphide (VHMS) deposits is considered to be related with the intra-oceanic stage of island arc(s) development in the Upper Ordovician–Middle Devonian based on the biostratigraphic record of ore-hosting sedimentary rocks. However, the direct Re-Os dating of four known VHMS systems in the Urals gives significantly younger Re-Os isochron ages ranging from 355 ± 15 Ma up to 366 ± 2 Ma. To address this discrepancy, we performed SHRIMP U-Pb dating on zircons extracted from rhyodacites (Eifelian biostratigraphic age of 393–388 Ma) from the footwall of the Alexandrinka VHMS deposit which has a Re-Os isochron age of sulphides of 355 ± 15 Ma. New 206Pb/238U mean age of 374 ± 3 Ma (MSWD = 1.4 and probability = 0.11) is considered to be the crystallisation age of the host volcanic rock. This age is ca. 15 Ma younger than the Eifelian (393–388 Ma) biostratigraphic age and overlaps the Frasnian–Famennian boundary (372 ± 2 Ma), characterised by the final stages of Magnitogorsk Arc – East European continent collision. Such an inconsistency with geochronological age may be due to a reburial of conodonts during resedimentation as a result of erosion of older rocks in younger sedimentary sequences.